Supply Chain Disruptions: Evidence from the Great East Japan Earthquake* - Carvalho, Vasco M; Nirei, Makoto; Saito, Yukiko U; Tahbaz-Salehi, Alireza (Quarterly Journal of Economics, 2021)
Abstract Exploiting the exogenous and regional nature of the Great East Japan Earthquake of 2011, this article provides a quantification of the role of input-output linkages as a mechanism for the propagation and amplification of shocks. We document that the disruption caused by the disaster propagated upstream and downstream along supply chains, affecting the direct and indirect suppliers and customers of disaster-stricken firms. Using a general equilibrium model of production networks, we then obtain an estimate for the overall macroeconomic impact of the disaster by taking these propagation effects into account. We find that the earthquake and its aftermaths resulted in a 0.47 percentage point decline in Japan’s real GDP growth in the year following the disaster.